ArtsEqual 2015–2021: The challenges of a Large-Scale Research Initiative in Finland - Karttunen, Sari; Houni, Pia (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
The article presents the ArtsEqual initiative, which is funded by the strategic research council of the Academy of Finland. The six-year project, funded from a sub-programme aiming to increase equality in society, is constructed on the visionary question: What if the arts were understood to be an essential part of public services? The project sets out to identify mechanisms and remove barriers that hinder equality from being established both within the arts and through them in society at large. The project is multidisciplinary and draws largely upon participatory, practice-led methodologies. It is carried out in six research teams and in two phases, the first of which consisted of numerous arts interventions combined with research. The conclusive phase that links the findings and experiences from the case studies together via qualitative system analysis started in the beginning of 2018. The authors are leaders of two of the research teams, and here they present the entire research initiative as well as exemplary sub-studies from their own teams. They discuss the research project and the preliminary findings in view of the changing role of the artist in society, a shared problematic between their teams. They also reflect on the advantages and challenges that programmatic funding may bring to artistic practices and research.